Formulation of entomopathogen Metarhizium anisopliae var. anisopliae bait to control subterranean termite, Coptotermes curvignathus holmgren (Blattodea: Rhinotermitidae) - Nyam, Vei Ting; Bong, Joseph Choon Fah; Ong, Kian Huat; King, Patricia Jie Hung (Pusat Sistematik Serangga, Universiti Kebangsaan Malaysia, 2021)
Coptotermes curvignathus is well known as the leading pest termite of agricultural and forestry tree crops. Termites are cryptic insects, hence their infestations can go undetected for years and this hinders the planters to carry out effective pest controls timely. This underscores the need for innovative forms of pesticides deployment. The use of bait is becoming a favorable approach that acts as edible ‘smart missiles’ to knock out the whole population of termites. To execute potent baiting in the field, effective bait matrix that able to preserve the effectiveness of the entomopathogenic agents impregnated and avoid the repellence of the targeted insect is sought-after in designing baits and this study aimed to formulate an entomopathogenic fungus Metarhizium anisopliae var. anisopliae based bait. Seven baits were formulated based on the pest feeding preferences and termites’ behavior studies. Additional substances were supplemented in the formulas as food sources and attractant to termites. Bait matrix made of dextrin, PVP K90 and skim milk (DPS) was found to be the most palatable to termites than other bait matrix tested. Termite took shorter time to finish the DPS bait with average 11.2 days and consumed significantly greater amount as compared to the other baits. DPS bait impregnated with M. anisopliae resulted closed to 100% mortality in 19 days. Based on shelflife bioassays, all formulated baits were able to maintain consistent termite mortality above 80% for over six months. The laboratory assessment had concluded that the formulated DPS bait was able to retain the effectiveness of the active entomopathogenic ingredient and appear palatable to C. curvignathus. Future field work should concentrate on the effectiveness of this bait in deterring pest resurgence.